The role of metallic impurities in oxide semiconductors: first‐principles calculations and PAC experiments - Errico, Leonardo Antonio (2004)
We report an ab-initio comparative study of the electric-field-gradient tensor (EFG) and structural relaxations introduced by acceptor (Cd) and donor (Ta) impurities when they replace cations in a series of binary oxides: TiO₂, SnO₂, and In₂O₃. Calculations were performed with the Full-Potential Linearized-Augmented Plane Waves method that allows us to treat the electronic structure and the atomic relaxations in a fully self-consistent way. We considered different charge states for each impurity and studied the dependence on these charge states of the electronic properties and the structural relaxations. Our results are compared with available data coming from PAC experiments and previous calculations, allowing us to obtain a new insight on the role that metal impurities play in oxide semiconductors. It is clear from our results that simple models can not describe the measured EFGs at impurities in oxides even approximately.